Exciton-coupled charge-transfer dynamics in a porphyrin J-aggregate/TiO 2 complex - Verma, Sandeep; Ghosh, Amrita; Das, Amitava; Ghosh, Hirendra Nath (Chemistry a European Journal, 2011)
Exciton-coupled charge-transfer (CT) dynamics in TiO2 nanoparticles (NP) sensitized with porphyrin J-aggregates has been studied by femtosecond time-resolved transient absorption spectroscopy. J-aggregates of 5,10,15-triphenyl-20-(3,4-dihydroxyphenyl) porphyrin (TPPcat) form CT complexes on TiO2 NP surfaces. Catechol-mediated strong CT coupling between J-aggregate and TiO2 NP facilitates interfacial exciton dissociation for electron injection into the conduction band of the TiO2 nanoparticle in pulse width limited time (<80 fs). Here, the electron-transfer (<80 fs) process dominates over the intrinsic exciton-relaxation process (J-aggregates: ca. 200 fs) on account of exciton-coupled CT interaction. The parent hole on J-aggregates is delocalized through J-aggregate excitonic coherence. As a result, holes immobilized on J-aggregates are spatially less accessible to electrons injected into TiO2, and thus the back electron transfer (BET) process is slower than that of the monomer/TiO2 system. The J-aggregate/porphyrin system shows exciton spectral and temporal properties for better charge separation in strongly coupled composite systems.